Using Branch Age and Diameter to Identify Woodland Management: New Developments. (3rd July 2018) - Out, Welmoed A.; Hänninen, Kirsti; Vermeeren, Caroline
ABSTRACT: Previous research involving models and age/diameter analysis of branches of modern trees has demonstrated the possibility of distinguishing between managed and unmanaged trees. These findings were then applied to waterlogged wood assemblages from archaeological contexts. The aim of this new study was to reinforce the validity of the models, also with respect to branches of greater diameter than those investigated previously, and to investigate the risk of confusing managed and unmanaged trees by investigating free-standing unmanaged trees, natural shoots of unmanaged trees, and managed trees subject to a long management cycle. The new results confirm that unmanaged trees can be distinguished from managed trees in the case of willow and ash, but show that correct distinction is more difficult in the case of alder. They further indicate that the models are valid for branches of up to at least 23 cm in diameter. The study of branches of free-standing unmanaged trees, natural shoots of unmanaged trees and managed trees with a long cycle demonstrated a substantial overlap in the age/diameter data between unmanaged and managed trees, leading to adjustment of the models. It is explained how branches of both unmanaged and managed trees can still be recognised in archaeological material.